Crematorium Baumschulenweg - Axel Schultes; Charlotte Frank (Oz, 2000)
“People die and they are not happy”—architecture can’t change that. A place of rest, a space for silence: that is something it still manages to provide, despite the fact that not even stones are as heavy as they were in more solid epochs with a firmer belief in the eternal, as in Saqqara, as in Giza, for example. Ed. note: Crematorium design by Schultes. Text by Charlotte Frank.